Ask a manager how to navigate clueless colleagues, lunch-stealing bosses, and the rest of your life at work - Green, Alison (London Piatkus, 2018)
From the creator of the popular website Ask a Manager and New York magazine's work-advice columnist comes a witty, practical guide to navigating 200 difficult professional conversations--featuring all-new advice! There's a reason Alison Green has been called "the Dear Abby of the work world." Ten years as a workplace-advice columnist have taught her that people avoid awkward conversations in the office because they simply don't know what to say. Thankfully, Green does--and in this incredibly helpful book, she tackles the tough discussions you may need to have during your career
Conversations with your boss -- Conversations with your coworkers -- Conversations when you're the boss -- Conversations with your job interviewer
1
Keywords: BUSINESS & ECONOMICS -- Careers; Conflict management; Conflict management; Interpersonal relations; Interpersonal relations; Psychology, Industrial; Psychology, Industrial; SELF-HELP -- Communication & Social Skills; SELF-HELP -- Personal Growth -- Success; Work environment; Work environment; Work -- Psychological aspects; Work -- Psychological aspects; Work -- Psychological aspects; Conflict management; Interpersonal relations; Organizational behavior; Psychology, Industrial; Work environment